An Analysis of Hijra Decisions in the Banking Sector in Padang City - Ghazela, Jehan Putri; Manzilati, Asfi; Muljaningsih, Sri (Journal of International Conference Proceedings, 2023)
The dual-banking system adopted by Indonesia shows the phenomenon of hijra in society which can be seen from the decrease in the number of loans and third-party funds in conventional banks. On the other hand, there has been an increase in financing and third-party funds in Islamic banks. The market share of Islamic banking in West Sumatra is 6.8% larger than the nation is only 5%, therefore this research was conducted in Padang City, West Sumatra Province. This study aims to analysis of hijrah decisions from conventional banks based on the Theory of Planned Behavior by Ajzen. The analytical method used in this study is Schultz's descriptive qualitative approach to phenomenology through the blade of "because of motives" and "order to motives". Data collection uses interview methods from key informants and supporting informants. Based on the results there are 4 themes have been found as follow: 1.) Spiritual belief; Bank interest is riba in Islam. 2.) Momentum; Relearning Qur'an. 3.) Temptation; Before and after the hijra. 4.) W